2002
DOI: 10.1177/135676670200800407
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of perceived differences in service quality — The case of health spas in Slovenia

Abstract: The authors concentrate on the importance of service quality elements in health spas. In the introduction the authors describe general characteristics of the health spa industry in Slovenia. They also point out the expanding emphasis on the service elements of products, their perceived quality and their influence upon the management practices of organisations. The main characteristics of the theoretical discussion on quality of services are presented, as well as the background of the research project. This 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 20 publications
2
31
0
5
Order By: Relevance
“…Respondent 2 (M, H) explained that, 'the role of service quality standards is to protect the interests of customers and to guarantee a minimum level of excellence'. To measure the quality of hot springs experience, previous studies have identified two key dimensions namely: functional quality (how the service was delivered) and technical quality (what was delivered) (Ferguson et al, 1999;Mueller and Kaufmann, 2001;Snoj and Mumel, 2002). A majority of respondents emphasised the functional aspects of the service rather than the technical aspects.…”
Section: Capabilities Of Destination Management Organizations Nearlymentioning
confidence: 99%
“…Respondent 2 (M, H) explained that, 'the role of service quality standards is to protect the interests of customers and to guarantee a minimum level of excellence'. To measure the quality of hot springs experience, previous studies have identified two key dimensions namely: functional quality (how the service was delivered) and technical quality (what was delivered) (Ferguson et al, 1999;Mueller and Kaufmann, 2001;Snoj and Mumel, 2002). A majority of respondents emphasised the functional aspects of the service rather than the technical aspects.…”
Section: Capabilities Of Destination Management Organizations Nearlymentioning
confidence: 99%
“…Similar problems are tackled by Snoj, Mumel, (2002) Deng, (2007, Hadzik, Szromek, (2013) Środa-Murawska, Grzelak-Kostulska, Biegańska, (2015 Albayrak, Caber, Bideci (2016).…”
Section: Introductionmentioning
confidence: 87%
“…Relatively common, the method is employed across numerous businesses and branches of industry, including tourism, where it has been used to assess the quality of services offered in travelling (Oh, 2011), hospitality, gastronomy (Lai, Hitchcock, 2015), as well as in health resorts and SPA and wellness destinations (e.g. Snoj, Mumel, 2002;Deng, 2007;Środa-Murawska et al, 2015). …”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…Se hizo necesaria la adaptación de los ítems, anadiendo unos yeliminando otros, para reflejar mejor las características específicas de cada servicio (Carman, 1990;Getty & Thompson, 1994). Se tomaron como referencia investigaciones anteriores relacionadas con el sector objeto de estudio y concretamente en turismo termal (Snoj;1995;Snoj & Mumel, 2002). El cuestionario final recoge 22 componentes de calidad de servi cio en establecimientos termales, medidos en una escala Likert de siete puntos, Siguiendo a Zeithaml et ai.…”
Section: Metodologíaunclassified